2022
DOI: 10.1039/d2ra03300c
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of luteolin in hydrophilic organic solvents and structure–antioxidant relationships of luteolin glycosides

Abstract: Efficient glycosylation of luteolin in organic solvents and the structure–antioxidant relationships of luteolin glycosides were reported for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Li et al revealed that D-α-tocopheryl polyethylene glycol 1000 succinate (TPGS)-coated liposomes provide an effective cancer chemotherapy strategy for model drugs with poor water solubility. Miyashita et al found that delivering luteolin through a microemulsion system can improve its oral bioavailability without affecting its metabolite profile [146,147]. These studies suggest that if the water solubility and bioactivity of luteolin are improved by some procedures, luteolin could be developed as a therapeutic drug to treat various inflammatory and cancerous diseases caused by inflammation or oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al revealed that D-α-tocopheryl polyethylene glycol 1000 succinate (TPGS)-coated liposomes provide an effective cancer chemotherapy strategy for model drugs with poor water solubility. Miyashita et al found that delivering luteolin through a microemulsion system can improve its oral bioavailability without affecting its metabolite profile [146,147]. These studies suggest that if the water solubility and bioactivity of luteolin are improved by some procedures, luteolin could be developed as a therapeutic drug to treat various inflammatory and cancerous diseases caused by inflammation or oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, enzymatic glycosylation in organic solvents provides some industrially attractive advantages, such as reversing the thermodynamic equilibrium of glycosidases hydrolysis reactions, improving the aqueous solubility of hydrophobic substrates, eliminating microbial contamination, and lowing industrial cost process. 20,21 By using this approach, solvent-stable glycosidase (b-fructosidase from Arthrobacter nicotianae) showed high activity and stability in hydrophilic organic solvents with more than 90% yield of puerarin glycosides. 20 In this study, we demonstrate that the solvent-stable bfructosidase can be efficiently used for the glycosylation of vitexin, and evaluate the anti-tumor activities of vitexin glycosides.…”
Section: Introductionmentioning
confidence: 99%